Influence of prison treatment on the re-education, rehabilitation, and social reincorporation of inmates of the Pocollay de Tacna penitentiary, period 2010-2012 - Supo García, Ritsy Marianella (2014)
Objetive: Determine the influence Correctional Treatment in fulfilling the rights of reeducation, rehabilitation and social reintegration of the inmates of the prison of Pocollay of Tacna, 2010-2012. Established the following hypothesis: in the prison of Pocollay of Tacna, prison Treatment compliance adversely affects the rights of reeducation, rehabilitation and social reintegration of prisoners, provided for in Article 139, paragraph 22 of the Constitution of Peru. Method: The research is a form of applied research, because it is oriented in the application of knowledge to the solution of a problem, as the theory confronts reality. It is also a type of Socio Legal Research that examines the events and relationships of social order governed by rules, which adopted the nonexperimental design (ex post facto) Description - Explanatory. For this purpose we considered the information obtained through the application of the questionnaire, and the Certificate of Interview. Result: The data were tabulated and analyzed using tables and graphs. After the phase of analysis and interpretation of the results was determined that: In the prison of Pocollay of Tacna, Prison Treatment compliance adversely affects. Conclusion: In the prison of Pocollay of Tacna, Prison Treatment compliance adversely affects the rights of re-education, rehabilitation and social reintegration of prisoners, period 2010 - 2012.